Pengaruh Non-Performing Financing Pembiayaan Mudharabah dan Musyarakah Terhadap Profitabilitas dengan Dimoderasi oleh Good Corporate Governance Pada Bank Umum Syariah di Indonesia: (The Effect of Non-Performing Financing Mudharabah and Musyarakah Financing on Profitability Moderated by Good Corporate Governance in Islamic Commercial Banks in Indonesia) - Deffa Salsabilah Rusyda; Masiyah Kholmi; Fahmi Dwi Mawardi (UPT Penerbitan Universitas Jember, 2023)
The purpose of this study is to analyze and test the effect of Non-Performing Financing on Mudharabah Financing and Musyarakah Financing on Profitability moderated by Good Corporate Governance in Islamic Commercial Banks in Indonesia for the 2017-2021 period. This study uses a population of all Islamic Commercial Banks in Indonesia for the 2017-2021 period. The sampling method in this study used a purposive sampling method. The data acquisition technique in this study uses secondary data, namely in the form of an annual report for Islamic Commercial Banks in Indonesia in the 2017-2021 period. The data analysis method used is Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA). The results of the study show that Non-Performing Financing of mudharabah financing and musyarakah financing simultaneously (Test F) has an effect on profitability and this study provides evidence that Non-Performing Financing of mudharabah financing and musyarakah financing has a negative and significant effect on Profitability in Islamic Commercial Banks. As well as Good Corporate Governance (GCG) can moderate Non-Performing Financing mudharabah financing and musyarakah financing on profitability.